PERSEPSI PETANI PADI ORGANIK DALAM PENERAPAN SISTEM PERTANIAN PADI ORGANIK DI KECAMATAN IMOGIRI, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Nurmalianik Nurmalianik; Suprih Sudrajat (JURNAL ILMIAH AGRITAS, 2022)
The research was conducted in the Madya Tani Group of Imogiri Subdistrict. This research aimed to find out how the perception of organic rice farmers in the application of organic rice farming systems and find out the factors that affect the perception of organic rice farmers in the application of organic rice farming system in Imogiri Subdistrict, Bantul Regency, Yogyakarta Special Region. This research is quantitative research, in which the population in this study is organic rice farmers in the Madya farming group. The location of the study was determined purposively (intentionally). Samples were determined using saturated sampling methods or census. The data analysis method in this study used multiple linear regression analysis. The results of this study showed that the perception of organic farmers in the application of organic farming systems was 86.42%, meaning that the perception of organic rice farmers in the application of organic rice farming systems is very high. Meanwhile, the factors that affect the perception of organic farmers in the application of organic farming systems included education, land area and experience.